Organizational learning in the implementation and adoption of national electronic health records: Case studies of two hospitals participating in the National Programme for Information Technology in England. (September 2014) - Takian, Amirhossein; Sheikh, Aziz; Barber, Nicholas
Objective: To explore the role of organizational learning in enabling implementation and supporting adoption of electronic health record systems into two English hospitals. Methods and setting: In the course of conducting our prospective and sociotechnical evaluation of the implementation and adoption of electronic health record into 12 "early adopter" hospitals across England, we identified two hospitals implementing virtually identical versions of the same "off-the-shelf" software (Millennium) within a comparable timeframe. We undertook a longitudinal qualitative case study–based analysis of these two hospitals (referred to hereafter as Alpha and Omega) and their implementation experiences. Data included the following: 63 in-depth interviews with various groups of internal and external stakeholders; 41-h on-site observation; and content analysis of 218 documents of various types. Analysis was both inductive and deductive, the latter being informed by the "sociotechnical changing" theoretical perspective. Results: Although Alpha and Omega shared a number of contextual similarities, our evaluation revealed fundamental differences in visions of electronic health record and the implementation strategy between the hospitals, which resulted in distinct local consequences of electronic health record implementation and impacted adoption. Both hospitals did not, during our evaluation, see the hoped-for benefits to the organization as a result of the introduction of electronic health record, such as speeding-up tasks. Nonetheless, the Millennium software worked out to be easier to use at Omega. Interorganizational learning was at the heart of this difference. Conclusion: Despite the turbulent overall national "roll out" of electronic health record systems into the English hospitals, considerable opportunities for organizational learning were offered by sequential delivery of the electronic health record software into "early adopter" hospitals. We argue that understanding the process of organizational learning and its enabling factors has the potential to support efforts at implementing national electronic health record implementation endeavors.